Living on the edge : essays on the Chittagong Hill Tracts - Bhaumik, Subir; Guhaṭhākuratā, Meghanā; Basu Ray Chaudhury, Sabyasachi (South Asia Forum for Human Rights ; Calcutta Research Group, 1997)
Contributed essays.